Tinjauan Yuridis Terhadap Tindak Pidana Penyalahgunaan Narkotika Berdasarakan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika - Raden Daru Fajar Nusantara; Aris Prio Agus Santoso; Peter Guntara; Evi Elisanti (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
This study aims to determine 1) the legal review of the crime of narcotics abuse based on Law Number 35 of 2009 concerning narcotics. 2) obstacles and law enforcement efforts against the crime of narcotics abuse based on Law Number 35 of 2009 concerning narcotics. This research method uses a normative legal approach with a prescriptive research type that focuses on literature studies. The data used are secondary data sourced from primary, secondary, and tertiary legal materials. The data collection technique is carried out through literature studies. The data analysis technique is carried out descriptively qualitatively with data reduction, data presentation, and drawing conclusions. The results of the study indicate that the study shows that Law Number 35 of 2009 has clearly regulated provisions regarding narcotics abuse and its sanctions. Obstacles to the crime of narcotics abuse are legal substance obstacles, legal structure obstacles, facilities and infrastructure obstacles, community legal culture obstacles and external factors such as technology and transnational networks. Law enforcement efforts against narcotics abuse crimes are classified into representative efforts, preventive efforts and rehabilitative efforts.